2020
DOI: 10.1021/acs.chemrev.0c00922
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotany and the Role of Plant Natural Products in Antibiotic Drug Discovery

Abstract: The crisis of antibiotic resistance necessitates creative and innovative approaches, from chemical identification and analysis to the assessment of bioactivity. Plant natural products (NPs) represent a promising source of antibacterial lead compounds that could help fill the drug discovery pipeline in response to the growing antibiotic resistance crisis. The major strength of plant NPs lies in their rich and unique chemodiversity, their worldwide distribution and ease of access, their various antibacterial mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
160
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 234 publications
(168 citation statements)
references
References 567 publications
1
160
0
7
Order By: Relevance
“…Information on the use of plant extracts in clinical trials was obtained from clinicaltrials.gov ( NLM, 2020 ). Based on the same literature search, we examined the antibacterial activities of plant-derived compounds in another review ( Porras et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Information on the use of plant extracts in clinical trials was obtained from clinicaltrials.gov ( NLM, 2020 ). Based on the same literature search, we examined the antibacterial activities of plant-derived compounds in another review ( Porras et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, by analyzing more than 183 natural products with antibacterial activity from plants, researchers found that plant natural products represent a promising source of antibacterial lead compounds that could help fill the drug discovery pipeline in response to the growing antibiotic resistance. [ 31 ]…”
Section: Introductionmentioning
confidence: 99%
“…Increased antibacterial activity can be attributed to the presence (in a large percentage) of oxygenated monoterpenes; they destroy the cell morphology and viability of the biofilm by increasing the permeability and reducing the polarization of the cytoplasmic membrane. Free hydroxyl (–OH) groups can release protons, leading to conformational changes and ultimately cell death [ 16 ].…”
Section: Introductionmentioning
confidence: 99%